Community-specific evaluation of tool affordances in wild chimpanzees - Gruber, Thibaud; Muller, Martin N. N.; Reynolds, Vernon; Wrangham, Richard W.; Zuberbühler, Klaus (My University, 2011)
The notion of animal culture, defined as socially transmitted community-specific behaviour patterns, remains controversial, notably because the definition relies on surface behaviours without addressing underlying cognitive processes. In contrast, human cultures are the product of socially acquired ideas that shape how individuals interact with their environment. We conducted field experiments with two culturally distinct chimpanzee communities in Uganda, which revealed significant differences in how individuals considered the affording parts of an experimentally provided tool to extract honey from a standardised cavity. Firstly, individuals of the two communities found different functional parts of the tool salient, suggesting that they experienced a cultural bias in their cognition. Secondly, when the alternative function was made more salient, chimpanzees were unable to learn it, suggesting that prior cultural background can interfere with new learning. Culture appears to shape how chimpanzees see the world, suggesting that a cognitive component underlies the observed behavioural patterns.